Problems and Solutions in Researching Computer Game Assisted Dialogues for Persons with Aphasia - Backman, Ylva; Gardelli, Viktor; Parnes, Peter (Designs for Learning, 2022)
In this paper, we describe technological advances for supporting persons with aphasia in philosophical dialogues about personally relevant and contestable questions. A computer game-based application for iPads is developed and researched through Living Lab inspired workshops in order to promote the target group’s communicative participation during group argumentation. We outline some central parts of the background theory of the application and some of its main features, which are related to needs of the target group. Methodological issues connected to the design and use of Living Labs with persons with aphasia are discussed. We describe a few problems with researching development of communicative participation during group argumentation using an app assisted intervention for the target group and suggest some possible solutions. Validerad;2022;Nivå 1;2022-03-28 (joosat); Funder: Luleå University and Technology, and the Municipality of Luleå (LTU-1033-2016)